Estimated production and evapotranspiration of irrigated bean cultivars - Santana, Márcio J. De; Lemos, Leandro B. [UNESP]; Souza, Stefany S. De; Campos, Talita M.; Silva, Flávia M. Da; Borges, Rafael D. (Associação Brasileira de Engenharia Agrícola, 2014)
The current study intended to determine the optimum water depth, yield and evapotranspiration (ETc) for bean cultivars. The experiment was conducted in the Campus of Unit I of the Triângulo Mineiro Federal Education and Technology Institute in Uberaba, MG, in a completely randomized design with three replications. The treatments consisted of four water-replacing levels in the soil (70, 100, 130 and 160% of the crop evapotranspiration) and four bean cultivars (Pérola, BRSMG Madrepérola, BRSMG Majestoso and IAC Alvorada). The average values of ETc obtained for soil water balance for the cultivars Pérola, BRSMG Madrepérola, BRSMG Majestoso and IAC Alvorada were, respectively, of 5.25 mm day-1, 4.59 mm day-1, 4.54 mm day-1 and 4.77 mm day-1. The water depths which provided the highest yields were for the cultivars Pérola, BRSMG Madrepérola, BRSMG Majestoso and IAC Alvorada of 451.61 mm, 454.41 mm, 504.71 mm and 344.30 mm, respectively. The maximum yields found were 4597.87 kg ha-1 (Pérola), 4546.27 kg ha-1 (BRSMG Madrepérola), 4253.39 kg ha-1 (BRSMG Majestoso) and 3958.50kg ha-1 (IAC Alvorada).

Objetivou-se determinar a lâmina ótima, a produtividade e a evapotranspiração (ETc) de cultivares de feijoeiro. O experimento foi conduzido no Câmpus da unidade I do Instituto Federal de Educação, Ciência e Tecnologia do Triângulo Mineiro, em Uberaba - MG, em um delineamento em blocos casualizados com três repetições. Os tratamentos foram constituídos de quatro níveis de reposição de água no solo (70; 100; 130 e 160% da evapotranspiração da cultura) e quatro cultivares de feijão (Pérola, BRSMG Madrepérola, BRSMG Majestoso e IAC Alvorada). Os valores médios de ETc obtidos pelo balanço de água no solo para as cultivares Pérola, BRSMG Madrepérola, BRSMG Majestoso e IAC Alvorada, foram, respectivamente, de 5,25 mm dia -1, 4,59 mm dia -1; 4,54 mm dia -1 m e 4,77 mm dia -1. As lâminas que proporcionaram as maiores produtividades foram para as cultivares Pérola, BRSMG Madrepérola, BRSMG Majestoso e IAC Alvorada, de 451,61; 454,41; 504,71 e 344,30 mm, respectivamente. As produtividades máximas encontradas foram 4.597,87 kg ha-1 (Pérola); 4.546,27 kg ha-1(BRSMG Madrepérola); 4.253,39 kg ha-1(BRSMG Majestoso) e 3.958,50 kg ha-1(IAC Alvorada).
Estimativa da produtividade e da evapotranspiração de cultivares de feijão irrigado
Keywords: Irrigation management; ETc; Optimum water depth; Phaseolus vulgaris L; Manejo da irrigação; ETc; Lâmina ótima; Phaseolus vulgaris L